Peningkatan Kinerja Karyawan Bagian Cutting Produksi melalui Disiplin Kerja dan Kepuasan Kerja pada PT XY - Sihombing, Grace Kezia; Rachmat Mulyana, Aam (IPM2KPE, 2024)
This study aims to understand the improvement of work discipline and job satisfaction on the performance of employees in the cutting production department of PT. XY. The data collection technique used a questionnaire with a sample of 33 employees in the cutting production department as respondents in this study. All tests were carried out using SPSS software version 26. The data analysis used was reliability, normality, validity, multicollinearity, multiple linear regression, heteroscedasticity, coefficient of determination R2, F Test, and T Test. Through multiple linear regression tests, the t-test achievement was obtained, namely 6.178> 2.042 with sig. 0.000 <0.05 on variable X1, therefore it can be stated that work discipline has an effect on employee performance but is not significant, then the t value is 2.056> 2.042 with sig. 0.049 <0.05 on variable X2, thus job satisfaction has a significant effect on employee performance. Keywords: Work Discipline, Employee Performance, Job Satisfaction